Proposing a Gaming Language Analysis Procedure to Reveal Video Game Ideology through Ludic Linguistics - Purnomo, SF Luthfie Arguby; Khristianto, Khristianto (Register Journal, 2019)
This study proposes a procedural analysis on the implementation of ludic linguistics to analyze gaming language with wordplays, the core of focus in ludic linguistics, as the point of departure. To formulate the procedural analysis, theories of language play by Crystal ideology of influence and ludonarrative model by Aarseth, wordplay in gaming context by Paul, intended meaning level by Stiles, wordplay transmission by Winter-Froemel, game interface types by Stonehouse and indexical storytelling by Fernández-Vara were applied as the theoretical foundation. To provide a vivid application of the proposed procedural analysis, wordplays appearing on game assets from Konami’s Metal Gear Solid, Metal Gear Solid 2: Sons of Liberty, and Metal Gear Solid 3: Snake Eater were taken as examples of analysis. The five steps procedure is able to show how wordplays in gaming context are designed as mechanical cues to help gamers complete the games and as narrative cues to help them comprehend the story. Further, this proposed procedure is able to indicate that the mechanical and narrative cues have particular ideology of influence, which affects gamers in reacting and responding to particular problems presented by the games. The result of this study discloses future research on the roles of wordplays in gaming context, signifying the importance of ludic linguistics as a bridge between language studies and game studies. Keywords: Wordplay; Gaming Language; Ludic Linguistics; Game Dtudies; Metal Gear Solid